Soil Moisture and Crop Yield Data for Jawe, Ethiopian Highlands - International Center for Tropical Agriculture; International Water Management Institute; Ethiopian Institute of Water Resources; Addis Adaba University; Mekelle University (International Food Policy Research Institute, 2018)
The data included in this study were a part of research that was conducted to assess the impacts of different land uses and soil water conservation (SWC) interventions on runoff and sediment yield at different scales in the highlands of Ethiopia. Run-off and soil loss data were collected from the experimental runoff plots that were set up to monitor daily runoff and sediment yield under different land use and management practices in Gudoberet Kebele (North Shewa). It includes data from four treatment plots?woodlot, grazing, cropland with (SWC) and cropland without SWC?with two replications that were established on 60 square meter area from 2014 to 2017.